2006
DOI: 10.1121/1.2161439
|View full text |Cite
|
Sign up to set email alerts
|

Mapping seabed variability: Rapid surveying of coastal regions

Abstract: Directional broadband reverberation can be exploited for rapidly probing seabed variability over large areas O ͑10 3 -10 4 ͒ km 2 ; the data need not be calibrated. Seabed variability thus mapped inherently combines spatial variability in geoacoustic properties that control reflection and those that control scattering. It is shown that in some cases, the variability can be separated. The method is applied to measurements in the Straits of Sicily where the data indicate the existence of two provinces where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…We make the assumption that the seabed reflection coefficient is constant along the track and from the track to the scattering patch. This assumption is based on a study of seabed variability, 23 that showed that this area is very nearly homogeneous with respect to the seabed properties ratio / ␣ 2 . While it is possible that this ratio is constant because changes in are always offset by changes in ␣, a simpler and more reasonable explanation is that the two quantities are nearly constant.…”
Section: Approachmentioning
confidence: 99%
“…We make the assumption that the seabed reflection coefficient is constant along the track and from the track to the scattering patch. This assumption is based on a study of seabed variability, 23 that showed that this area is very nearly homogeneous with respect to the seabed properties ratio / ␣ 2 . While it is possible that this ratio is constant because changes in are always offset by changes in ␣, a simpler and more reasonable explanation is that the two quantities are nearly constant.…”
Section: Approachmentioning
confidence: 99%
“…17 The sound speed was nearly isovelocity but slightly downward refracting. The sound speed profiles measured during the experiment are plotted in gray in Fig.…”
Section: Scarab98 Real Data Resultsmentioning
confidence: 98%
“…IV, results are provided for simulated and real data collected during the SCARAB98 (Ref. 17 and CLUTTER09 experiments in the Malta plateau region of the Mediterranean Sea. The performance of the WI-MVF is studied in both known and uncertain environments.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][13][14][15][16] Due to its simplicity and intuitive nature, the energy flux method has further been developed and widely used for SW reverberation calculations, 17-30 mainly due to works by Harrison,Holland and Ainslie. 18,20,21,[23][24][25][26][27][28][29][30] All the closed-form expressions in isovelocity shallow water, derived by Zhou, 6 Harrison, 18 Ainslie 27,30 and Holland, 24 are almost identical, having only minor differences in constant coefficients. In this paper, Zhou's closed-form expressions for reverberation in isovelocity water are used to extract the frequency and angular dependence of the BBS at LF&LGA from long-range reverberation data.…”
Section: The Closed-form Expressions For Ocean Reverberation Intementioning
confidence: 85%